Pengembangan Alat Pendeteksi Masker Di Era New Normal Dengan Warning Tones - Citra Devi Nurmala; Harun Sujadi (Universitas Sains dan Teknologi Komputer, 2021)
COVID-19 is a virus that has been declared a pandemic by WHO, and in Indonesia itself has designated COVID-19 as a national disaster through Presidential Decree No. 12 of 2020. The main source of transmission of this virus comes from respiratory droplets, one of which is to prevent its spread by using mask. Currently, the government is implementing a new normal. Even though they are active in an external environment, health protocols must be followed and the whole community must be disciplined in living them. In this study, a mask detection device was developed in the new normal era with warning tones. The research method used is the Prototype method, starting from problem identification, literature study, system requirements analysis, system design, testing and implementation. The results of face detection accuracy obtained face detection accuracy at a distance of 0-30 cm as a whole that is equal to 100%.